2017
DOI: 10.1111/cdev.12958
|View full text |Cite
|
Sign up to set email alerts
|

Optimism as a Candidate Health Asset: Exploring Its Links With Adolescent Quality of Life in Sweden

Abstract: This study aims to understand the role that optimism could play in the context of a health asset approach to promote adolescent health-related quality of life (HRQOL). Adolescents (n = 948), between 11 and 16 years old from a medium-sized rural town in Sweden, answered questionnaires measuring optimism, pessimism, and HRQOL. The findings indicate a significant decrease in optimism and a significant increase in pessimism between early and midadolescence. The study has allowed us to present associational evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…Such programs could also aim to enhance adolescents' perspective-taking and future-oriented thinking, given that reported excitement for the future and being able to imagine their life 5 years into the future were identified as important protective factors in this study. Interestingly, previous research on adolescent mental health and quality of life has found that optimism for the future, being able to set goals, and plan for future possibilities are important health assets for adolescents that could inform adolescent health promotion strategies (Haggstrom Westberg et al, 2019), while future-oriented thinking has been associated with better reflective decision-making in adolescence (Eskritt et al, 2014). The protective role of sleeping 8 to 10 h per night (unadjusted models only) is not surprising, given that previous research has documented the relationship between sleep hygiene including hours of sleep and mental health issues, increased risk-taking behaviours, poor decision-making, and impairments in cognitive control among adolescents (Palmer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Such programs could also aim to enhance adolescents' perspective-taking and future-oriented thinking, given that reported excitement for the future and being able to imagine their life 5 years into the future were identified as important protective factors in this study. Interestingly, previous research on adolescent mental health and quality of life has found that optimism for the future, being able to set goals, and plan for future possibilities are important health assets for adolescents that could inform adolescent health promotion strategies (Haggstrom Westberg et al, 2019), while future-oriented thinking has been associated with better reflective decision-making in adolescence (Eskritt et al, 2014). The protective role of sleeping 8 to 10 h per night (unadjusted models only) is not surprising, given that previous research has documented the relationship between sleep hygiene including hours of sleep and mental health issues, increased risk-taking behaviours, poor decision-making, and impairments in cognitive control among adolescents (Palmer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that young people with a more optimistic tendency about their future present more behaviors related to good health (Klimusová et al, 2016) and less risk of experiencing psychopathological symptoms (Xiong et al, 2020). Being dispositional optimism a cognitive resource whose origin could occur during adolescence (Zou et al, 2016), some evidence has suggested that a more optimistic orientation in young people could be an essential health asset (Häggström et al, 2017), which could function as a protective factor against psychopathological conditions such as depression (Ames et al, 2015). Empirically, it has been shown that dispositional optimism during adolescence is associated with a better perception of internal locus of control and this, in turn, is related to more adaptive selfregulation (Renaud et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto al efecto sobre la salud física en la infancia, algunas investigaciones proponen que el optimismo infantil contribuye a una mejor calidad de vida en niños y niñas que experimentan dolor corporal debido a algún tipo de enfermedad (häggström et al, 2017;Williams, Davis, hancock y Phipps, 2009). una explicación general a la relación entre el optimismo y la salud física está orientada a aspectos conductuales que intervienen en ésta, como mejor disposición al tratamiento, mejor manejo de los desafíos físicos, mayor sensación de autoeficacia y comportamientos más saludables que contribuyen a la mejoría del estado de salud física (Williams, Davis, hancock y Phipps, 2009).…”
Section: Consecuencias Del Optimismo En La Infanciaunclassified